PERENCANAAN SISTEM DRAINASE PASAR JOHAR SEMARANG - Arif Wicaksono; Pungky Dwi Saputra; Hari Budieny; Abdul Kadir (Jurnal Karya Teknik Sipil, 2013)
As trade area which is located in the north of the Semarang City, Johar is an area prone to flood. That's because the drainage canal superficiality clog due to garbage, the channel capacity is not large enough and the pump capacity is not sufficient. Johar is at a height that is almost equal to the sea surface which land subsidence periodically, so as to Johar area, water flows through a drainage pump with Kali Semarang as an elongated catch. The method we used to handle the flood of Pasar Johar is by calculating the flood discharge, isolate the area around the elevation of the road which serves as a dike, enlarge the channel that is not enough, enlarge the channel that is not enough and made sluice in preparation if the pump can not operated. From the calculation, some channels have increased flow capacity. Type of partner channels with bony concrete / precast planned to increase the capacity of Existing stream channel is the channel type C with a width of 1000 mm and 1000 mm high channels. There are 5 channel capacity should be increased. To remove the water from the drainage channel used pumps which located in the drainage pump house. Pump house planned 3 units main pump installed and 1 unit reserved. Maximum discharge for each pump is  0.35 m3/second. Drainage channels connected to the house by using the channel pump. When only light rain occurred, simply lit one pump only. While in the event of heavy rain, so can lit two or three pumps. Thus the application of more efficient pump. Time waster channels streamed to Semarang with waste pipe from the pump drainage. Waste pipe is made with galvanized materials with elements lighter than steel and stainless steel. Based on the calculations, the total cost for the Design of  Johar Drainage System  is 8,471,009,500.00 rupiah.